ORIENTASI PEMAHAMAN TEKSTUALITAS AL-QUR’AN: KRITIK DAN PROYEKSI PEMAHAMAN BARU ATAS PEMIKIRAN NASR HAMID ABU ZAID DI UNIVERSITAS PTIQ JAKARTA - Nur Arfiyah Febriani; Wifayatul Aamani; Endah Dewi Lestari; Otong Surahman; Ikhlas Budiman; Abdul Hafid (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This paper examines Nasr Hamid Abu Zaid’s thought on the textuality of the Qur'an, offering a new approach to understanding the Qur'an as both a cultural and a revelatory text. Employing a literature review method, this study explores the origins of the concept of textuality in linguistics and literary studies, its application in Qur'anic studies, and provides a critical analysis of Abu Zaid’s ideas. The findings reveal that Abu Zaid’s textual approach opens possibilities for a more contextual and dynamic reading of the Qur'an while maintaining its sacred status as divine revelation. Nevertheless, this approach has been criticized for potentially obscuring the transcendental dimension of revelation. The study projects the need for a new approach that reconciles the sacred, historical, and social dimensions of the Qur'an to ensure that the understanding of the sacred text remains authentic and relevant in the context of modern times